Emotional stress increases GluA2 expression and potentiates fear memory via adenylyl cyclase 5 - Qian Yang; Ahmad Abdulla; Muhammad Farooq; Yoshihiro Ishikawa; Siqiong June Liu (Cell Reports)
Summary: Stress can alter behavior and contributes to psychiatric disorders by regulating the expression of the GluA2 AMPA receptor subunit. We have previously shown in mice that exposure to predator odor stress elevates GluA2 transcription in cerebellar molecular layer interneurons (MLIs), and MLI activity is required for fear memory consolidation. Here, we identified the critical involvement of adenylyl cyclase 5, in both the stress-induced increase in GluA2 in MLIs and the enhancement of fear memory. We found that noradrenaline release during predator odor stress activates AC5 and downstream PKA-CREB signaling. This pathway interacts synergistically with α1-adrenergic receptors to promote synaptic GluA2 expression in MLIs. At a behavioral level, predator odor stress potentiates associative fear memory, and this is abolished in AC5 knockout mice, suggesting that AC5-dependent plasticity is required for enhanced memory formation. Therefore, AC5 is a promising pharmacological target for preventing stress-enhanced fear memory.